A novel dynamic stability analysis method for jointed rock slopes based on block-interface interaction. (June 2021) - Gao, Lin'gang; Li, Tongchun; Liu, Xiaoqing; Qi, Huijun; Fan, Shujie; Lin, Chaoning; Zhou, Minzhe
Abstract: The dynamic stability evaluation of jointed rock slopes is a complex problem of solving nonlinear and uncertain systems. The interactive method of partitioned finite element and interface element is applied to the solution of the seismic response of jointed rock slopes under earthquake. The contact status of the weak interlayer can be calculated at each moment by the method. Since the balance of the slope slider can be inferred by contact status on weak interlayer, a novel criterion of rock slope instability based on the contact status of the contact surface is proposed. The criterion not only satisfies the requirement for the sudden change of residual deformation but also meets the completely broken of the weak interlayer. Since the interactive method can still converge in the state of slope failed, an adaptive strength reduction method is proposed to search for the safety factor automatically. To verify the effectiveness of the method, the dynamic stability of a classical rock jointed slope is calculated, and then compared with the result in the reference paper. Moreover, the proposed method is applied to analyze the dynamic stability of a high steep rock slope with complex internal joints and the safety factor is calculated successfully.